2015
DOI: 10.1002/cctc.201500050
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Hydrogen Peroxide over Au‐Pd Catalyst—The Effect of Co‐Solvent Addition

Abstract: Direct synthesis represents a green alternative, an environmentally benign process for the production of hydrogen peroxide. This is a three‐phase reaction, a solid catalyst with gas reactants and a liquid phase, which collects hydrogen peroxide formed from the catalyst surface. The choice of solvent and/or addition of promoters has a significant effect on the reaction rates observed, as well as selectivity towards peroxide. In addition to non‐toxic water, short chain alcohols are very attractive, due to good s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…[39,41] With Paunovic et al providing a comprehensive study on the choice of co-solvent. [42] In particular, methanol has been widely studied as a co-solvent, due to increased reactant solubility but also as it results in the suppression of H2O2 decomposition. [35] Furthermore, the key role of the solvent has been recently elucidated by Wilson and Flaherty, with the presence of protic solvents, such as water and methanol shown to be key to H2O2 production.…”
Section: Resultsmentioning
confidence: 99%
“…[39,41] With Paunovic et al providing a comprehensive study on the choice of co-solvent. [42] In particular, methanol has been widely studied as a co-solvent, due to increased reactant solubility but also as it results in the suppression of H2O2 decomposition. [35] Furthermore, the key role of the solvent has been recently elucidated by Wilson and Flaherty, with the presence of protic solvents, such as water and methanol shown to be key to H2O2 production.…”
Section: Resultsmentioning
confidence: 99%
“…The evident acceleration effect of EtOAc in the system is another issue to be investigated. According to the literature, organic solvents could improve conversion yields and selectivity of chemical reactions by increasing interactions between reactants and catalyst surfaces . We speculate that the accelerated antimicrobial function of EtOAc in the solution systems is caused by its good affinity with both MSB and E.…”
Section: Resultsmentioning
confidence: 80%
“…According to the literature, organic solvents could improve conversion yields and selectivity of chemical reactions by increasing interactions between reactants and catalyst surfaces. 46 We speculate that the accelerated antimicrobial function of EtOAc in the solution systems is caused by its good affinity with both MSB and E. coli bacteria cells, which could serve as a good media by shortening the distance between the bacterial cells and the photoactive aromatic ketones (marked in red in Figure 3a) and promoting contacts between the short-lived triplets or ROS with the bacteria cells. The shortened distance enables the biocidal ROS and oxidative triplet states to diffuse effectively to the target microbes, 47−49 resulting in more efficient microbial inactivation.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Previous evidence from the bulk gold powder-catalyzed reaction suggested that the first step involved the oxidative dehydrogenation of the amine substrate to give the imine (2) [38,39]. In this and subsequent oxidation steps, it is assumed that H2O is the coproduct because H2O2 was not detected in the final reaction mixture; moreover, H2O2 would likely decompose to H2O and O2 under the conditions of the reaction [52].…”
Section: Reaction Pathways For the Formation Of Lactams From Cyclic Smentioning
confidence: 99%